Renal glomerular number and size in Australian aborigines, African Americans and white populations from the same locations - Bertram, John F. (Image analysis and stereology, 2001)
End stage renal disease is a major health problem for Australian Aborigines and African Americans. Abnormally enlarged glomeruli are commonly observed in biopsies from Aborigines and African Americans and may represent a compensatory hypertrophic response to reduced nephron endowment. We have commenced a study examining glomerular number and size, and their associationsin Australian Aborigines and whites, and US African Americans and whites. Kidneys at autopsy are perfusion-fixed and subsampled for stereological estimation of total glomerular number (Nglom; using the physicaldisector/fractionator combination), and mean renal corpuscle (Vcorp) and glomerular volume (Vcorp). Kidneys from 58 people have been studied to date with ages ranging from newborn to 84 years. Preliminary findings are: (1)an almost 9-fold range in Nglom (from 210,332 to 1,825,380) with a mean of 762,302; (2) Nglom decreased with age in adult life (p = 0.014); (3) Vcorp varied 19-fold in the series and 5.5-fold in adults; (4) Vglom was inversely correlated with Nglom (p = 0.004); (5) total renal corpuscle volume (Nom X Vcorp) ranged by a factor of 13.2; (6) kidney weight was correlated with body surface area (BSA) at all ages (p < 0.001); (7) BSA-corrected kidney weight did not vary with age, it ranged from 47 g/m2 to 175 g/m2, a 3.7 fold difference, with an average of 92 +- 25 g/m2. These preliminary results have revealed several new and important correlations. No racial differences in glomerular number or size have yet been identified, but with greater sample sizes such differences may be revealed.
Keywords: Kidney glomerulus; Ledvični glomerul; Slika, obdelava s pomočjo računalnika; Anatomy and histology; Avstralija; Image processing, computer-assisted; Ethnic groups; Etnične skupine; Australia; Združene države Amerike; United states; aborigini; glomeruli; ledvice; anatomija; ledvične bolezni